Conservation Agriculture Effects on Soil Water Holding Capacity and Water-Saving Varied with Management Practices and Agroecological Conditions: A Review - Abdallah, Ahmed M.; Jat, Hanuman Sahay; Choudhary, Madhu; Abdelaty, Emad F; Sharma, Parbodh Chander; Jat, Mangi Lal (MDPI, 2021)
Improving soil water holding capacity (WHC) through conservation agriculture (CA)-practices, i.e., minimum mechanical soil disturbance, crop diversification, and soil mulch cover/crop residue retention, could buffer soil resilience against climate change. CA-practices could increase soil organic carbon (SOC) and alter pore size distribution (PSD); thus, they could improve soil WHC. This paper aims to review to what extent CA-practices can influence soil WHC and water-availability through SOC build-up and the change of the PSD. In general, the sequestered SOC due to the adoption of CA does not translate into a significant increase in soil WHC, because the increase in SOC is limited to the top 5–10 cm, which limits the capacity of SOC to increase the WHC of the whole soil profile. The effect of CA-practices on PSD had a slight effect on soil WHC, because long-term adoption of CA-practices increases macro- and bio-porosity at the expense of the water-holding pores. However, a positive effect of CA-practices on water-saving and availability has been widely reported. Researchers attributed this positive effect to the increase in water infiltration and reduction in evaporation from the soil surface (due to mulching crop residue). In conclusion, the benefits of CA in the SOC and soil WHC requires considering the whole soil profile, not only the top soil layer. The positive effect of CA on water-saving is attributed to increasing water infiltration and reducing evaporation from the soil surface. CA-practices’ effects are more evident in arid and semi-arid regions; therefore, arable-lands in Sub-Sahara Africa, Australia, and South-Asia are expected to benefit more. This review enhances our understanding of the role of SOC and its quantitative effect in increasing water availability and soil resilience to climate change.